Monogenic diabetes mellitus due to defects in insulin secretion (Swiss Medical Weekly, 2012)
Monogenic forms of diabetes mellitus cover a heterogeneous group of diabetes which are uniformly caused by a single gene mutation and are characterised by impaired insulin secretion of the pancreatic beta cell. It is estimated that they account for up to 5% of all cases of diabetes mellitus, which are often not diagnosed or are misclassified as type 1 or 2 diabetes. However, accurate diagnosis is important because of the special implications for treatment, prognosis and family risk. The knowledge of typical clinical features such as mode of inheritance, age at diagnosis and impaired insulin secretion, as well as genetic testing establishes the diagnosis of MODY, mitochondrial diabetes and neonatal diabetes.